An alternative way to break the matrix barrier: an experimental study of a LIFU-mediated, visualizable targeted nanoparticle synergistic amplification for the treatment of malignant fibroblasts - Zhao, Xiangzhi; Fan, Zhengchao; Zhou, Junan; Li, Ying; Zhu, Weiwei; Su, Song; Xia, Jizhu (Frontiers in Bioengineering and Biotechnology, 2024)
Malignant fibroblasts (MFs) are widely present in various diseases and are characterized by connective tissue proliferation; these cells act as a physical barrier that severely limits drug delivery and affects disease outcomes. Based on this, we constructed the smart, integrated, theranostic, targeted lipid nanoprobe HMME-RG3@PFH to overcome the bottleneck in the early diagnosis and treatment of MF-related diseases. The protein glucose transporter protein 1 (GLUT-1) is overexpressed on MFs, and its ideal substrate, ginsenoside RG3 (RG3), significantly enhances the targeted uptake of HMME-RG3@PFH by MFs in a hypoxic environment and endows the nanomaterial with stealthiness to prolong its circulation. Perfluorohexane (PFH), a substance that can undergo phase change, was encapsulated in the lipid core and vaporized for ultrasound-enhanced imaging under low-intensity focused ultrasound (LIFU) irradiation. Moreover, hematoporphyrin monomethyl ether (HMME) was loaded into the lipid bilayer for photoacoustic molecular imaging and sonodynamic therapy (SDT) of MFs under the combined effects of LIFU. Additionally, HMME-RG3@PFH instantaneously burst during visualization to promote targeted drug delivery. In addition, the increased number of exposed RG3 fragments can regulate the MFs to enter a quiescent state. Overall, this nanoplatform ultimately achieves dual-modal imaging with targeted and precise drug release for visualization and synergistic amplification therapy, providing a new possibility for the early diagnosis and precise treatment of MF-related diseases.